PEMBERDAYAAN KELOMPOK TANI BUDI KARYA DESA AMPUKUNG KECAMATAN KALUA KABUPATEN TABALONG - Reno Affrian (Administraus, 2022)
Abstract : This study aims to determine (1) the Empowerment of the Budi Karya Farmer Group, Ampukung Village, Kalua District, Tabalong Regency, (2) Factors that affect the Empowerment of the Budi Karya Farmer Group, Ampukung Village, Kalua District, Tabalong Regency. The research method uses a qualitative descriptive approach, with a philosophical foundation. postpositivesme, Determination of informants purposively ( purposeful) , Data collection techniques Interview, Observation and Documentation. The analysis technique used is data condensation, data display, verification. The results of the study 1. The empowerment of the Budi Karya Farmer Group in Ampukung Village, Kalua District, Tabalong Regency has not been fully optimal, it can be seen from. Enabling is an effort to build power that encourages, motivates and raises awareness of the potential of the community as well as efforts to develop. In the case of the Budi Karya Farmers Group, Ampukung Village, it has been able to help increase the potential of farmers in terms of the use of assistive devices such as thresher machines, spray machines, pumping machines, and other assistance from other agencies, although support and motivation from other agencies is still minimal. Empowering this with opportunities that make the community more empowered, in the case of the cultural farmer group in its empowerment it is quite optimal, judging from the potential opportunities for the largest Ampukung village that is farming, Protecting is defending the interests of the community, Protecting has not been fully carried out by the government, there is no mechanism that has been implemented. protect farmers when farmers fail to harvest. (1) Driving Factors a. Community Social, b. Community Economy, (2) Inhibiting Factors a. Sustainability Support, b. Coordination between Organizations. Suggestion The need to improve coordination between the farmer groups with the village and local governments, it is necessary to increase empowerment in collaborative activities so that the goals can be achieved as expected. Keywords: Community Empowerment, Development, Farmer Groups Abstrak : Penelitian ini bertujuan untuk mengetahui (1) Pemberdayaan Kelompok Tani Budi Karya Desa Ampukung Kecamatan Kalua Kabupaten Tabalong, (2) Faktor yang mempengaruhi Pemberdayaan Kelompok Tani Budi Karya Desa Ampukung Kecamatan Kalua Kabupaten Tabalong, Metode penelitian menggunakan pendekatan deskriptif kualitatif, dengan landasan filosifis postpositivesme, Penentuan informan secara purposive (bertujuan) , Teknik Pengumpulan data Wawancara, Observasi dan Dokumentasi. Teknik Analisa yang digunakan adalah data condensation, data display, verification. Hasil penelitian 1. Pemberdayaan Kelompok Tani Budi Karya Desa Ampukung Kecamatan Kalua Kabupaten Tabalong belum sepenuhnya optimal hal tersebut diliat dari. Enabling adalah upaya membangun daya mendorong, memotivasi dan membangkitkan kesadaran akan potensi yang dimiliki masyarakat serta upaya untuk mengembangkan. pada kasus Kelompok Tani Budi Karya Desa Ampukung sudah mampu membantu meningkatkan potensi petani dalam hal penggunaan alat bantu seperti mesin perontok, mesin semprot, mesin pompa, serta bantuan lainnya dari dinas lainnya, walaupun dukungan dan motivasi dari dinas lain masih minim. Empowering berkaitan dengan peluang yang membuat masyarakat semakin berdaya, pada kasus kelompok tani budi karya dalam pembedayaannya sudah terliat cukup optimal peluang dilihat dari peluang potensi keadaan desa ampukung mayoritas masyaraikat yang Bertani, Protecting adalah membela kepentingan masyarakat, Protecting belum belum sepenuhnya dilakukan oleh pemeintah, belum ada mikanisme yang melindungi petani saat petani gagal panen. (1) Faktor Pendorong a. Sosial Masyarakat, b.Ekonomi Masyarakat, (2) Faktor Penghambat a. Dukungan Keberlanjutan, b. Koordinasi antar Organisasi. Saran Perlunya peningkatan koordinasi antara kelompok tani budi karya dengan pemerintah desa dan pemerintah daerah, perlu peningkatan pemberdayaan yang menekankan pada kegiatan koloboratif sehingga tujuan pemberdayaan dapat dicapai sebagaimana mestinya. Kata Kunci: Pemberdayaan Masyarakat, Pembangunan, Kelompok Tani